Ecosystem services provided by aculeate wasps. (29th April 2021) - Brock, Ryan E.; Cini, Alessandro; Sumner, Seirian
ABSTRACT: The aculeate wasps are one of the most diverse and speciose insect taxa; they are omnipresent across ecosystems and exhibit diverse co‐evolutionary and exploitative associations with other organisms. There is widespread conjecture that aculeate wasps are likely to perform essential ecological and economic services of importance to the health, well‐being and nutritional needs of our planet. However, the scope and nature of the ecosystem services they provide are not well understood relative to other insect groups (e.g. bees, butterflies, beetles); an appreciation of their value is further tarnished by their public reputation as pointless pests. Here, we conduct the first comprehensive review of how aculeate wasps contribute to the four main areas of ecosystem services: regulatory, provisioning, supporting and cultural services. Uniting data from a large but previously disconnected literature on solitary and social aculeate wasps, we provide a synthesis on how these insects perform important ecosystem services as parasites, predators, biological indicators, pollinators, decomposers and seed dispersers; and their additional services as a sustainable alternative to meat for human consumption, and medicinal potential as sources of research leads for anti‐microbials and cancer treatments. We highlight how aculeate wasps offer substantial, but largely overlooked, economic benefits through their roles in natural pest management and biological control programs. Accordingly, we provide data‐driven arguments for reasons to consider the ecosystem service value of aculeate wasps on a par with other 'useful' insects (e.g. bees). Finally, we provide a research roadmap identifying the key areas of research required to capitalise better on the services provided by these important insects.